2019
DOI: 10.1128/jcm.00274-19
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 8 and Pentaxin (C-Reactive Protein) as Potential New Biomarkers of Bovine Tuberculosis

Abstract: Bovine tuberculosis (bTB) is caused by Mycobacterium bovis. During the early stage of infection, greater than 15% of M. bovis-infected cattle shed mycobacteria through nasal secretions, which can be detected by nested PCR. To compare the differences in the protein profiles of M. bovis-infected cattle that were nested PCR positive (bTBPCR-P) and M. bovis-infected cattle that were nested PCR negative (bTBPCR-N) and to screen for biomarkers that will facilitate the early and accurate detection of bTB, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
2
22
1
Order By: Relevance
“…World Health Organization pointed out that human TB can only be controlled by eradicating bTB (22). An efficient way to eradicate bTB is to slaughter M. bovis-infected cattle, and prioritizing the slaughter of bTB cattle that actively shed mycobacteria was recommended (23). An even more urgent need is to reveal the immune heterogeneity of bTB in different stages, and to develop and apply improved diagnostic techniques for active bTB to prevent them from transmitting bTB.…”
Section: Discussionmentioning
confidence: 99%
“…World Health Organization pointed out that human TB can only be controlled by eradicating bTB (22). An efficient way to eradicate bTB is to slaughter M. bovis-infected cattle, and prioritizing the slaughter of bTB cattle that actively shed mycobacteria was recommended (23). An even more urgent need is to reveal the immune heterogeneity of bTB in different stages, and to develop and apply improved diagnostic techniques for active bTB to prevent them from transmitting bTB.…”
Section: Discussionmentioning
confidence: 99%
“…The permanence of neutrophils at the site of injury depends on the production of chemical mediators, such as TNF-α [ 44 ]. Nonetheless, recent studies associate it mostly with interleukin-8 (IL8) [ 45 ], a potential marker for M. bovis infections [ 46 ]. Neutrophils arrive in two “waves”, the first relates to the innate response against the pathogen and the second to the adaptive response [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several promising cytokine/chemokine biomarkers of M. bovis infection and disease in domestic and wildlife species have been revealed in recent years, in addition to the widely recognized host biomarker IFN-γ. These include, although are not limited to, IP-10, IL-1β, IL-4, IL-8, IL-17A, CXCL9, IL-10, and IL-22 (37,40,(78)(79)(80)(81)(82)(83)(84). Both protein and gene expression assays have been used to assess biomarker levels in different species and have facilitated identification of additional targets for diagnostic development (5).…”
Section: Cytokine/chemokine Biomarkers Of Mycobacterium Bovis Infectionmentioning
confidence: 99%
“…The precise role of the chemokine IL-8 in TB has not been fully elucidated, although studies have demonstrated IL-8 binding to tubercle bacilli and interactions with the pathogen that appear to enhance mycobactericidal characteristics of macrophages and neutrophils (131). Increased IL-8 is also required for granuloma formation (84). (39).…”
Section: Il-8mentioning
confidence: 99%